Francisella tularensis: FupA mutation contributes to fluoroquinolone resistance by increasing vesicle secretion and biofilm formation - Claire Siebert; Helena Lindgren; Sabrina Ferré; Corinne Villers; Sandrine Boisset; Julien Perard; Anders Sjöstedt; Max Maurin; Céline Brochier-Armanet; Yohann Couté; Patricia Renesto (Emerging Microbes and Infections, 2019)
ABSTRACTFrancisella tularensis is the causative agent in tularemia for which the high prevalence of treatment failure and relapse is a major concern. Directed-evolution experiments revealed that acquisition of fluoroquinolone (FQ) resistance was linked to factors in addition to mutations in DNA gyrase. Here, using F. tularensis live vaccine strain (LVS) as a model, we demonstrated that FupA/B (Fer-Utilization Protein) expression is linked to FQ susceptibility, and that the virulent strain F. tularensis subsp. tularensis SCHU S4 deleted for the homologous FupA protein exhibited even higher FQ resistance. In addition to an increased FQ minimal inhibitory concentration, LVSΔfupA/B displayed tolerance toward bactericidal compounds including ciprofloxacin and gentamicin. Interestingly, the FupA/B deletion was found to promote increased secretion of outer membrane vesicles (OMVs). Mass spectrometry-based quantitative proteomic characterization of vesicles from LVS and LVS∆fupA/B identified 801 proteins, including a subset of 23 proteins exhibiting differential abundance between both strains which may therefore contribute to the reduced antibiotic susceptibility of the FupA/B-deleted strain. We also demonstrated that OMVs are key structural elements of LVSΔfupA/B biofilms providing protection against FQ. These results provide a new basis for understanding and tackling antibiotic resistance and/or persistence of Francisella and other pathogenic members of the Thiotrichales class.